La gobernanza turística, un impacto para el aprovechamiento sostenible de los recursos naturales y culturales de la parroquia Pastocalle, provincia de Cotopaxi, año 2019 - Toapanta Viracocha, Angélica Fernanda (2020)
The aim of this research is to establish the current tourist governance system of Pastocalle parish in order to demonstrate the management and improve it to use the natural and cultural resources in a better way to develop the local tourism. The origin of the study is preceded by the comprehensive analysis of the management of the Autonomous Decentralized Government of the Pastocalle Parish, identifying several limitations that can be improved for the benefit of local tourism, for which the research is defined with a qualitative approach by the information that is investigated and interpreted the same that was obtained through the application of a structured interview, In this sense, the research responds to a hypothetical - deductive methodology in which a holistic analysis of the governance of the parish on tourism is carried out. In effect, after having investigated, a participatory management model is proposed focused on the good use of tourist resources with the purpose of linking the different levels of government for the sustainable use of the benefits that have the parish, this model is mainly based on citizen participation as a primary axis for the identification of needs and the formulation of projects that can solve the problem. Finally, the last chapter of the research corresponds to a compendium of everything analysed in the research in which the results and their scope are presented.